AB0084 Elevated levels of il-37 are associated with tophus and suppressed the production of inflammatory cytokines in patients with gout. (12th June 2018) - Hong, X.; Ding, L.; Huang, Q.; Liu, D.
Abstract : Background: IL-37 has been identified as a natural inhibitor of innate immunity. Although increasing evidence shows elevated IL-37 expression in various autoimmune diseases, its correlation with clinical symptoms in gout is still unclear. Objectives: This study aims to determine the correlation between the levels of IL-37 and clinical indexes in gout patients, and to examine the inhibitory effect of IL-37 on pro-inflammatory cytokine including IL-1β, IL-6 and IL-18 from peripheral blood mononuclear cells (PBMC) of gout patients in culture. Methods: Levels of serum IL-37 and concentrations of IL-1β, IL-6, IL-18 in cell culture from 42 patients with gout and 40 healthy controls (HCs) were measured by enzyme-linked immunoassay (ELISA). Moreover, the relative mRNA expression of these cytokines in PBMCs was detected by real-time PCR (RT-PCR). The correlations between serum IL-37 levels and clinical values in gout patients were analysed by Spearman correlation test. Results: Both protein and mRNA levels of IL-37 were higher in gout patients than healthy controls, especially in patients with tophus. Serum IL-37 levels of gout patients were positively correlated with C-reactive protein and uric acid. Furthermore, the expression of IL-1β, IL-6 and IL-18 in PBMCs from gout patients was significantly increased, which were markedly suppressed by IL-37 in culture. Conclusions: Serum levels of IL-37 are closely associated with clinical symptoms in gout patients and may represent a potential biomarker for the disease activity. References: [1] Richette P, Bardin T. Gout. Lancet2010;375(9711)318–28. [2] Masters SL, Simon A, Aksentijevich I, Kastner DL. Horror autoinflammaticus: the molecular pathophysiology of autoinflammatory disease. Annu Rev Immunol2009;27(2009)621–68. [3] Martinon F, Petrilli V, Mayor A, Tardivel A, Tschopp J. Gout-associated uric acid crystals activate the NALP3 inflammasome. Nature2006;440(7081)237–41. [4] Emmerson BT. The management of gout. N Engl J Med, 1996;334(7)445–51. [5] Fiechtner JJ, Simkin PA. Urate spherulites in gouty synovia. JAMA1981;245(15)1533–6. Disclosure of Interest: None declared